Counter-Hegemonic Decision Premises in Commons-Based Peer Production: A Degrowth Case Study - Ben Robra; Alex Pazaitis; Kostas Latoufis (tripleC: Communication, Capitalism & Critique)
Capitalism is evidently the main cause of ecological degradation, climate change and social inequality. Degrowth as a counter-hegemony opposes the capitalist imperatives of economic growth and capital accumulation and radically seeks to transform society towards sustainability. This has strong political economic implications. Economic organisations and modes of production are essential in overcoming capitalist hegemony. This article investigates two commons-based peer production (CBPP) organisations in a qualitative case study by asking how they could align with degrowth counter-hegemony to help overcome capitalism. Social systems theory is used as an organisational lens to empirically research decision premises and their degrowth counter-hegemonic alignment. The results show that this alignment is possible in relatively small organisations. However, to help degrowth succeed, CBPP needs to be more widely adopted, for which larger organisations seem better equipped. Future studies focusing on the concept of scaling wide in CBPP networks in the context of degrowth counter-hegemony are suggested.